The Influence of Organizational Culture and Work Ability on Employee Performance in CV. Laju Bersama Furniture Tanjung Morawa - Hadi Panjaitan; Jopinus Saragih; Demak Manik (PT Inovasi Pratama Internasional, 2022)
This study aims to determine whether organizational culture and work ability both partially and simultaneously have a significant effect on employee performance at CV. Laju Bersama Furniture and how much influence it has. The method used in this study is a quantitative method with several tests, namely reliability analysis , classical assumption deviation test and linear regression . Based on the regression results of the primary data processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 16.243 + 0.171 X 1 + 0.420 X 2. Partially, organizational culture variable (X 1 ) has a significant effect on employee performance (Y) at CV. Maju Bersama Furniture. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (2.498 > 1.978). While the work ability variable (X 2 ) has a significant influence on employee performance (Y) at CV. Laju Bersama Furniture. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (5.381 > 1.978). Simultaneously, organizational culture variables (X 1 ) and work ability (X 2 ) have a significant influence on employee performance (Y) at CV. Laju Bersama Furniture. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (18.753 > 3.06). Organizational culture variables (X 1 ) and work ability (X 2 ) are able to contribute to the influence of employee performance variables (Y) by 22.1% while the remaining 77.9% are influenced by other variables not examined in this study. From the conclusions above, the authors suggest that employees and leaders should further improve the organizational culture within the internal company so that it becomes a corporate culture and characteristic.